2013
DOI: 10.1002/ppsc.201300034
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of pH‐Tunable Calcium Phosphate Nanocapsules via Dendrimer‐Templated Assembly for Intracellular Lysosomal Release of Drugs

Abstract: A pH‐responsive dendrimer templated polymer‐calcium phosphate core shell nanostructure is developed. Upon exposure to cellular lysosomal pH, a guest anticancer drug is released from the nanocapsule by dissolution of the CaP shell. Such a stimuli responsive carrier enables on‐demand controlled release of drugs in acidic organelles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…18,30 Furthermore, the oxidation of CNT results in breaking of sp 2 backbone carbons and leads to formation of various (CQO, COOH or C-O-C) functional groups on the CNT surface. 29 The encapsulation efficiency of DOX in CNT-GSH-G4-CaP-DOX was found to be 385 mg g À1 (an average of n = 3 batches). 30 As the treated CNTs have open ends and their exterior and interior surfaces are both hydrophilic, it is expected that aqueous solutions containing drugs can flow into the inner cavity of CNTs, especially with the help of sonication.…”
Section: Synthesis and Characterization Of Cnt-g4-gsh-cap-doxmentioning
confidence: 97%
See 1 more Smart Citation
“…18,30 Furthermore, the oxidation of CNT results in breaking of sp 2 backbone carbons and leads to formation of various (CQO, COOH or C-O-C) functional groups on the CNT surface. 29 The encapsulation efficiency of DOX in CNT-GSH-G4-CaP-DOX was found to be 385 mg g À1 (an average of n = 3 batches). 30 As the treated CNTs have open ends and their exterior and interior surfaces are both hydrophilic, it is expected that aqueous solutions containing drugs can flow into the inner cavity of CNTs, especially with the help of sonication.…”
Section: Synthesis and Characterization Of Cnt-g4-gsh-cap-doxmentioning
confidence: 97%
“…18 Although various CNT based drug delivery or controlled release systems have been developed, in most of these systems, the bioactive compounds to be delivered are attached through covalent or noncovalent binding to the CNT surface, leaving the inner cavity unutilized. 29 One of the advantages of using dendrimer as a template is its nanoscale size and the 3-D spherical morphology which allows easy formation of CaP nanocapsules. This is because the drug is protected from the physiological environment as its prelude bio-availibilty and selected release allows for lower drug loading through effective intracelluar site delivery.…”
Section: Introductionmentioning
confidence: 99%
“…1d). 36,37 Fig. 1 (a) Schematic of the reversible pH-responsive Fe 3 O 4 -capped mesoporous silica ensembles with an acid-labile triazaadamantane linker.…”
Section: Ph-responsive Therapymentioning
confidence: 99%
“…[14][15][16][17][18][19][20] Of these pH-responsive drug carriers,t he development of CaPbased nanocarriers has shown that they are potentialc andidates for intracellular drug delivery because CaP remains stable at physiologicalpH, but dissolves rapidly in an acidic endosomal( pH 5.0) or lysosomal (pH 4.5) environment, which leads to fast releaseo fa nticancerd rugs. [21] Moreover,a s am ajor component of bones and teeth, CaP exhibits extraordinary biocompatibility,s uperiorb iodegradability,a nd is nontoxic, [22,23] which makes it suitable for drug delivery.T od ate, researches have reported the use of organic amphiphilic polymers,d endrimers, or adenosine 5'-triphosphate as templates for CaP-based nanocarriers [24][25][26][27][28] to avoid the problemsa ssociated with the direct synthesis CaP NPs. However,t he above approachesh ave suffered from some limitations, such as ac omplicated synthesis process, the use of toxic organics olvents, large diameters, and av ery low drugc apacity.T oa ddress the abovec hallenges, and inspired by our previous study, [29] we used PAA, ap H-responsive material, as at emplate to prepare PAA/CaP NPs with dualp H-responsiveness and ah igh drugloading capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, as a major component of bones and teeth, CaP exhibits extraordinary biocompatibility, superior biodegradability, and is nontoxic, which makes it suitable for drug delivery. To date, researches have reported the use of organic amphiphilic polymers, dendrimers, or adenosine 5′‐triphosphate as templates for CaP‐based nanocarriers to avoid the problems associated with the direct synthesis CaP NPs. However, the above approaches have suffered from some limitations, such as a complicated synthesis process, the use of toxic organic solvents, large diameters, and a very low drug capacity.…”
Section: Introductionmentioning
confidence: 99%